PENGGUNAAN PUPUK ORGANIK SISA BAGLOG JAMUR TIRAM PADA TANAMAN JAGUNG MANIS - Ikhsan Hasibuan (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2015)
One of important aspects in organic agriculture is availability of fertiliser that could be madefrom resources around the farm. Waste of oyster mushroom is a great potential to be developed in to organic fertiliser to be applied in organic sweet corn. To discover this challenge, an experiment had been done in Seginim, South Bengkulu. Nine dosage levels were tested and the results showed that the growth and yield of sweet corn were gained by using 4 tons of oyster mushroom organic fertiliser plus combined with 50 kg of NPK chemical fertiliser per hektar. We concluded that waste of oyster mushroom could be used as organic fertiliser and might be used for organic sweet corn.Keywords: sweet corn, oyster mushroom, waste, organic fertiliser